Ovarian Follicular Dynamics, and Hormonal and Biochemical Profile in Post-Pubertal and Postpartum Jaffrabadi Buffaloes - Raval, Rupesh J; Parmar, Kiran H; Dhami, Arjun J; Kavani, Fulabhai S (Indian Journal of Veterinary Sciences and Biotechnology, 2022)
Jaffrabadi buffalo is one of the heaviest buffalo breeds of the world (800 kg) and is known for poor reproductive efficiency. There is a scarcity of normal physiological data regarding reproductive parameters of Jaffrabadi buffalo. The primary objective of this study was to elucidate ovarian follicular dynamics, hormonal and biochemical profiles in 10 post-pubertal heifers (n=5 each of age 42±2 and 48±2 months) and five >90 days postpartum lactating buffaloes. Ultrasound monitoring of ovaries of animals was done at weekly interval and all follicles with diameter <4 mm (small follicles), 4-8 mm (medium follicles) and >8 mm (large follicles) as well as CLs identified were recorded. Blood samples were also collected soon after each USG from all animals for assay of hormonal and biochemical profiles. The findings revealed that the average number of small, medium and large follicles, total number of follicles per ovary as well as diameters of largest and subordinate follicles varied greatly among periods between three groups. The size of corpus luteum ranged from 13.7 to 21.2 mm, 13.7 to 23.9 mm and 15.3 to 22.7 mm, respectively, in Group-I, II and III. In the first week of study, significantly higher (p <0.05) average numbers of small follicles in Group-I and III, and medium follicles and total numbers of follicles in Group-III were observed as compared to other groups. The diameter of largest follicles and subordinate follicles were non-significantly different among all groups at all periods of the study. Plasma estrogen levels were significantly higher (p <0.05) in Group-I as compared to Group-III and Group-II on first and second week, however, it increased significantly (p <0.05) in Group-II and I on fourth week of study period. Plasma insulin concentrations were significantly (p <0.01) lower in buffaloes (Group-III) than in heifers (Group-I and II) throughout the study period, while plasma total cholesterol and total protein levels were higher in Group-III on 3rd to 5th weeks of study. Further, there were no significant differences in the plasma FSH, LH, progesterone and blood glucose levels in animals of three groups between periods at any of the week. The ultrasonographic and endocrine profile suggested establishment of cyclicity with silent ovulation. However, the behavioural estrus was still not manifested by these post-pubertal heifers and postpartum lactating buffaloes. These results are helpful to diagnose anovulatory conditions and/or true anestrus and initiate estrus synchronization protocols for early conception in Jaffrabadi buffaloes.